Clinical variations of double mesiodens: a review and case report - Villavicencio, Judy Elena; Hernández-Silva, Jesús Alberto; Medina-Cárdenas, Sebastián (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Supernumerary teeth are dental anomalies of number that, due to their prevalence, raise concerns among dentists, parents, and patients. They can occur isolated or associated with a syndrome and can lead to complications in eruption, occlusion, and patients’ appearance. Mesiodens are the most common type of supernumerary teeth and usually occur in the midline of the maxilla, between the two central incisors. Early diagnosis and prompt treatment of supernumerary teeth is important to prevent complications in permanent dentition. This article discussesthe clinical variations of mesiodens and reports three cases of fully-erupted double mesiodens.